Entrepreneurial opportunities for sports tourism based on Iran\'s geographical climate - Taghi Ashouri; Morteza Dosti; Seyed Mohamad Hosein Razavi; Abolhasan Hoseini (تحقیقات کاربردی علوم جغرافیایی)
The aim of this study is to identify and rank entrepreneurial opportunities in sports tourism based on geographical capabilities and capacities in Iran. The present study was descriptive-survey and was performed by mixed method. Data collection in this study was done in two stages. In the first phase, a list of entrepreneurial opportunities of sports tourism was identified through a search of previous research, as well as interviews with 17 people. In the next step, experts' opinions on these statements were obtained using the Delphi method. Finally, eight subfields of entrepreneurial opportunities are ranked based on Iran's geographical capacity in four temperate and humid climates, hot and humid, cold and mountainous, hot and dry, using a software program and a multivariate regression test. Based on the results, it can be said that along with economic, political, cultural factors, etc., the diversity of climate and geographical capacities is effective in the emergence and selection of opportunities. By analyzing the data, we can say that each of these opportunities has been used with different levels in Iran's four climates. Some opportunities in one climate take precedence over others. Authorities of tourism and sport in their short-term and long-term planning and planning should be instrumental in improving sport tourism by these opportunities.